Pectin-coated boron nitride nanotubes: In vitro cyto-/immune-compatibility on RAW 264.7 macrophages - Rocca, Antonella; Marino, Attilio; Del Turco, Serena; Cappello, Valentina; Parlanti, Paola; Pellegrino, Mario; Golberg, Dmitri; Mattoli, Virgilio; Ciofani, Gianni (Biochimica et biophysica acta, 2016)
Boron nitride nanotubes (BNNTs) represent a new opportunity for drug delivery and clinical therapy. The present work has the objective to investigate pectin-coated BNNTs (P-BNNTs) for their biocompatibility on macrophage cultures, since these cells are among the first components of the immune system to interact with administered nanoparticles. As first step, the potential toxicity of P-BNNTs is verified in terms of proliferation, oxidative stress induction and apoptosis/necrosis phenomena. Thereafter, the modulation of immune cell response following P-BNNT exposure is evaluated at gene and protein level, in particular focusing on cytokine release. Finally, P-BNNT internalization is assessed through transmission electron microscopy and confocal microscopy. The results proved that P-BNNTs are not toxic for macrophages up to 50μg/ml after 24h of incubation. The cytokine expression is not affected by P-BNNT administration both at gene and protein level. Moreover, P-BNNTs are internalized by macrophages without impairments of the cell structures. Collected data suggest that P-BNNTs cause neither adverse effects nor inflammation processes in macrophages. These findings represent the first and fundamental step in immune compatibility evaluation of BNNTs, mandatory before any further pre-clinical testing. [Display omitted] •Pectin-coated boron nitride nanotubes (BNNTs) have been prepared and tested on RAW 264.7 macrophages.•This study represents the first investigation of BNNT immune compatibility.•Collected data indicate the absence of acute toxicity and no adverse immune response.•The suitability of BNNTs for biomedical applications is confirmed.